Physical stabilization of a sandy lateritic soil using ceramic wastes - de Lima, Jairo Salim Pinheiro [UNESP]; Vicente, Gabriela Oliveira [UNESP]; Fagundes, Luiza Perroni [UNESP]; Cabral, Cássio Lázaro Barros [UNESP]; da Cruz, Felipe Augusto [UNESP]; Tashima, Mauro Mitsuuchi [UNESP] (FapUNIFESP (SciELO), 2020)
The growth of the cities has brought with environmental, social and economic problems, doing an aware-ness of sustainable development essential for the survival of humanity and for the preservation of the envi-ronment. In this way, it is important to highlight the amount of waste from construction and waste from the red ceramic industry and the significant growth of both in the last years. An alternative to this waste is its use in layers of pavements. The aim of this paper is to assess the possibility of use red ceramic wastes in the stabilization of a sandy lateritic soil. For that, three different percentages of ceramic wastes (0, 50 and 60%, in mass) were assessed and the influence of compaction energy was verified by California Bearing ratio (CBR) test. The obtained results showed that the use of ceramic wastes is a viable practice in the soil stabilization and, the enhancement on the energy compaction can improve significantly the CBR, yielding increment of 50% for samples containing 60% of ceramic waste.
Estabilização física de solo laterítico arenoso utilizando resíduos cerâmicos
Keywords: Red ceramic; Reuse of wastes; Soil stabilization